Aluminum hypophosphite and aluminum phenylphosphinate: A comprehensive comparison of chemical interaction during pyrolysis in flame-retarded glass-fiber-reinforced polyamide 6. (May 2019) - Cheng, Xi; Wu, Jianming; Yao, Chenguang; Yang, Guisheng
This study compared thermal degradation, pyrolysis behavior, and the fire behavior of flame-retarded glass-fiber-reinforced polyamide 6 with aluminum hypophosphite and aluminum phenylphosphinate (BPA-Al), respectively. We sythesize aluminum phenylphosphinate by benzenephosphinic acid (BPA) and AlCl3.6H2O in water. so we call aluminum phenylphosphinate BPA-Al for short. The dependence of limiting oxygen index on phosphorus content was linear for aluminum hypophosphite and BPA-Al. Thermogravimetric analysis proved aluminum hypophosphite was less stable than BPA-Al. Thermogravimetric-Fourier transform infrared tests showed that aluminum hypophosphite system balanced the charring process and the gas releasing well, and that BPA-Al system enhanced the charring process and decreased the gas releasing. Peak heat release rate and total heat release data proved that aluminum hypophosphite system was superior to BPA-Al system in lowering the heat release. Their differences were caused by different P-H (aluminum hypophosphite) and P-phenyl (BPA-Al) structures. P-H structure did better than P-phenyl structure in balancing the condensed phase effect and the gaseous phase action. So P-H structure (aluminum hypophosphite) was more suitable than P-phenyl structure (BPA-Al) in the flame retardancy of glass-fiber-reinforced polyamide 6.